Otoneurological Abnormalities in Patients with Friedreich's Ataxia - Zeigelboim,Bianca Simone (2017)
Abstract Introduction Friedreich's ataxia is a neurodegenerative disease and progressive by nature. It has autosomal recessive inheritance and early onset inmost cases. Nystagmus and hearing loss (in some cases) make up some of the common symptoms seen in this disorder. Objective The objective of this study is to examine vestibular disorders in patientswith Friedreich ataxia. Methods We conducted a retrospective cross-sectional study. We evaluated 30 patients with ages ranging from six to 72 years (mean age of 38.6 ( 14.7). The patients underwent the following procedures: anamnesis, ENT, and vestibular evaluations. Results Clinically, the patients commonly had symptoms of incoordination of movement (66.7%), gait disturbances (56.7%), and dizziness (50%). In vestibular testing, alterations were predominantly evident under caloric testing (73.4%), gaze nystagmus testing (50.1%), rotational chair testing (36.7%), and optokinetic nystagmus testing (33.4%). The presence of alterations occurred under examination in 90% of subjects, with the majority occurring in those with central vestibular dysfunction (70% of the examinations). Conclusion The most evident neurotological symptoms were incoordination of movement, gait disturbances, and dizziness. Alterations in vestibular examinations occurred in 90% of patients, mostly in the caloric test, with a predominance of deficient central vestibular system dysfunction.